CLONING AND EXPRESSION ANALYSIS OF THE PLASTIDIC FRUCTOSE-1,6-BISPHOSPHATASE CODING SEQUENCE FROM POTATO - CIRCUMSTANTIAL EVIDENCE FOR THE IMPORT OF HEXOSES INTO CHLOROPLASTS - Sonnewald, Uwe; et al. (Planta, 1992)
A copy DNA encoding the plastid-located isoform of the fructose-1,6-bisphosphatase (cp-FBPase) has been cloned from potato (Solanum tuberosum L.). Sequence analysis reveals a high degree of homology to cp-FBPases from wheat, spinach, and Arabidopsis. Analysis of RNA blots shows that the expression of the cp-FBPase is limited to green tissue such as leaf and stem, and is absent from photosynthetically inactive tissue such as roots, tubers and stolons. This provides additional evidence that hexoses or hexose phosphates are imported into amyloplasts of heterotrophic tissues. Incubation of detached leaves of potato in darkness in a sucrose-containing medium leads to massive accumulation of both starch and transcripts encoding starch biosynthetic enzymes. However, no transcripts encoding the cp-FBPase are detectable under these conditions.
Keywords: CALVIN CYCLE; CHLOROPLAST; FRUCTOSE-1; 6-BISPHOSPHATASE; SOLANUM (CHLOROPLAST); SUCROSE INDUCTION